Esclavos de Obraje : Consuelo en la Devoción. La cofradía de la Santa Veracruz Nueva fundada por Mulatos, Mestizos y Negros. Coyoacán, siglo XVII - Rosa Elena Rojas (Centre de Recherches sur les Mondes Américains, 2012)
One sunny morning of May, 1638, a group of mulattoes, mestizos and blacks got together in assembly, looking for both the ecclesiastical and royal authorizations to conform a brotherhood of discipline, under the auspice of the Dominican friars of the Saint John The Baptist Parish in Coyoacan, Mexico. Still in the collective memory, there are the revolts of slaves and the array of prohibitions for people of these races of the past recent years. Nevertheless, the group of faithful devotees opens the solemn procession of Holy Thursday and the brotherhood of Spaniards and the rest of people from the village complete the formation. What types of coexistence amongst black slaves, free African descendents, indigens and Spanish can be noticed after the study of the Rules, Registry and Regulations Book of this brotherhood ? Was their contact brief ? Which events influenced the control of brothers affiliated ? A closer look to the Spanish institution of religious brotherhoods as a region of refuge, physical and untangible at the same time, leads the reader to the rescue of some of the profane and religious yearnings of these blood brothers.